Isolation and screening of lipolytic fungi from the surface of pineapple (Ananas comosus) for extra-cellular lipase activity - Balce, Esther Virginia S. (2004)
ABSTRACT Coating pineapple with coconut oil to delay senescence and prevent chilling injury alters fruit flavor indicating hydrolytic rancidity. This might be attributed to lipases from yeasts and molds. Twenty-five distinct fungal colonies were collected from the pineapple's surface and qualitatively screened for extra-cellular lipase (ECL) production using precipitation method. Eleven isolates tested positive in the screening and subsequently identified to genus level using morphology. The lipase activities were then measured using quantitative titrimetric analysis. Both screenings demonstrated the ability of the fungal lipases to hydrolyze esters of oleic acid. Aspergillus, Penicillium, and Fusarium spp. exhibited the highest lipase activity. Rhizopus, Trichoderma, and Geotrichum spp. had the least lipase activity.